Dentoalveolar comparative study between removable and fixed cribs, associated to chincup, in anterior open bite treatment - Fernando César Torres; Renato Rodrigues de Almeida; Renata Rodrigues de Almeida-Pedrin; Fernando Pedrin; Luiz Renato Paranhos (University of São Paulo, 2012)
OBJECTIVE: The aim of this prospective study was to compare the dentoalveolar effects produced by two types of palatal crib, removable (Rpc+C) and fixed (Fpc+C), combined with chincup in growing patients with anterior open bite. MATERIAL AND METHODS: each group comprised 30 patients, in the mixed dentition phase, with similar cephalometric characteristics and skeletal ages. Group 1 (Rpc+C) presented initial mean age of 8.3 years and mean anterior open bite of 4.0 mm. Group 2 (Fpc+C) presented initial mean age of 8.54 years and mean anterior open bite of 4.3 mm. The evaluation period comprised 12 months between initial (T1) and second lateral radiograph (T2). The T2-T1 changes were compared cephalometrically in the 2 groups using the non-paired t-test. RESULTS: Vertical changes in the posterior dentoalveolar region were similar between the groups (about 1 mm) and no significant differences were found in molar mesialization. The Fpc+C group had in average 1.6 mm more improvement of the overbite as a result of greater maxillary incisor extrusion (1.3 mm). Patients in this group also presented less lingual tipping of maxillary incisors and more mandibular incisors uprighting. CONCLUSIONS: The Fpc+C combination was more efficient in the correction of the negative overbite mainly due to greater extrusion of the maxillary incisors. However, the Rpc+C appliance promoted better upper and lower incisor inclination, resulting in a more adequate overjet.